La comunicación efectiva en la relación de padres e hijos de 2 a 7 años con discapacidad auditiva profunda - López Mendoza, Erika Mariana (2021)
Faced with this problem, the opportunity and relevance arise to generate an investigative process to explore, analyze and describe the factors that affect the correlation between the learning of the Ecuadorian sign language and effective communication between parents and children with profound hearing disabilities. In the local context, parents and representatives of children with profound hearing disabilities from the Municipal School of Hearing and Language, in the city of Guayaquil, show a constant concern over the fact of not knowing fully the Ecuadorian sign language they require. your children to communicate in the family environment............